Edukasi Mengenai Aspek Genetik Pengobatan Kesehatan Mental dan Pola Asuh yang Mengurangi Tingkat Stres Pada Anak - Miranti Dwi Hartanti; Liza Chairani; Lilis Khairani; Denova Putri Apriliana Gumesna; Adharia Yogustri (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The psychological and emotional state of children's mental health include mental stability, stress tolerance, and the capacity to manage everyday challenges. In essence, parents want what's best for their child, which includes not making parenting blunders. This activity seeks to educate youngsters about the hereditary components of mental health treatment and parental techniques that lower stress levels in kids. The implementation strategy consists of in-person seminars and assessments of parents' understanding using pretests and posttests. The waiting room at Muhammadiyah Hospital Palembang's Children's Polyclinic served as the venue for this counselling session. The average knowledge of parents/caregivers among participants increased, according to the findings of the pre-post counselling test, both on parenting techniques that lower children's stress levels and genetic aspects of mental health therapy. Mental diseases can occur as a result of genetic variables like polymorphism and epigenetics. Apart from genetic considerations, extrinsic variables like parenting and family dynamics can also have an impact on children's mental health. The conclusion of the course on the genetics of mental health treatment and stress-reduction parenting is highly helpful for parents/caregivers.